Modulation of ex-vivo uterine contraction by the methanol leaf extract of Alchornea laxiflora Benth. (Euphorbiaceae) and preliminary spectrometric identification of associated secondary metabolites - Enitome E. Bafor; Juliet K. Nwogu; Uloma B. Elvis-Offiah; Fabian Amaechina; Josephine Ofeimun; Buniyamin Ayinde; Osemelomen Omoruyi; Christina Viegelmann; RuAngelie Edrada-Ebel (AOSIS, 2018)
Background: The leaves of Alchornea laxiflora are traditionally used in the south of Nigeria to prevent preterm births.   Aim: This study was designed to investigate the activity of A. laxiflora on uterine contractility.   Setting: The leaves of the plant were collected from forests in Egor, Benin City, Nigeria.   Methods: The leaves were cleaned and extracted in methanol. The extract (0.005 mg/mL-3.5 mg/mL) was tested on spontaneous uterine contraction and on oxytocin-induced contraction in normal and Ca2+-free media. The plant extract (0.0035 mg/mL, 0.035 mg/mL, 0.35 mg/mL and 3.5 mg/mL) was tested on high KCl-induced uterine contractions (80 mM). The plant extract (3.5 mg/mL) was also studied in the presence of amiodarone and glibenclamide in separate experiments. Mass spectrometric analysis was additionally performed on the plant extract in order to identify significant secondary metabolites that may have contributed to the activity of the plant.   Results: The plant extract inhibited spontaneous, oxytocin and high KCl-induced uterine contractions and also significantly inhibited (p < 0.01) oxytocin-induced uterine contraction in Ca2+-free medium. The plant extract significantly inhibited (p < 0.01 and p < 0.05) oxytocin's amplitude in the presence of amiodarone and glibenclamide, respectively. Secondary metabolites belonging to classes of fatty acids, glycols, terpenes, flavonoid glycosides and porphyrins were identified.   Conclusion: Alchornea laxiflora inhibited mouse uterine contractility possibly through interaction with potassium and calcium channels. Of the known metabolites identified, 3-deoxy-arabino-hept-2-ulosonic acid, 17-hydroxyingenol and phaeophorbide-a methyl inhibit uterine contractility and may contribute to the activity of A. laxiflora in utero.